Analisis perilaku pencegahan keputihan berdasarkan teori health promotion model (HPM) pada siswi kelas SMA - Marwiyah, Siti Wahidah; Siregar, Sri Astuti; Kasyani, Kasyani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Reproductive health is a major concern among adolescents. According to Word Health Organization (WHO) 45% of women experience vaginal discharge at least twice, and 90% of Indonesian women are at risk, highlighting the need for prevention. Purpose: To analyze vaginal discharge prevention behavior based on the health promotion model (HPM) theory in high school female students. Method: A cross-sectional design involving 152 students selected through simple random sampling. Primary data are collected using questionnaires measuring vaginal discharge prevention behavior and HPM-related factors. Data analysis uses the Chi-Square test. Results: Most respondents are 17 years old, with an even distribution across classes. A significant relationship exists between self-motivation, perceived benefits, and self-commitment with preventive behavior (